Concept of Human Rights - Mishra, Roopal (Trinity Law Review, 2023)
The recognition of a well maintained state lies on the maintenance of the rights in it. It is considered often on the basis of happiness of men in a society. The term Human Rights which has been known for the ages as ‘Natural Rights’ or in a more sophisticated way ‘Rights of Man’. It is a general notion that Human Rights is a western concept which initially originated from ‘Magna Carta’ of 1215. After that it was followed by Petition of Rights 1628, then Bill of Rights 1688 which then developed into American Bill of Rights 1791 and the French Declaration of Rights of Man 1789. Eleanor Roosevelt suggested the term Human Rights instead of Natural Rights for the first time. The term ‘Human Rights’ is accepted by the Universal Declaration of Human Rights in 1947 which was passed on 10th December 1948. Humans by virtue of them being human posses some rights, rational and independent and are inalienable in nature. Human Rights are birthright so they are inherent in each and every individual irrespective of caste, creed, colour, sex, religion and nationality. They are also referred as Fundamental Rights or Basic Rights.
Keywords: Human; nationality